2016
DOI: 10.3354/dao02959
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, site and tissue preference of myxozoan parasites infecting gills of cultured fish in Punjab (India)

Abstract: Native carp species cultured in Indian farms in Punjab (catla Catla catla, rohu Labeo rohita, mrigal Cirrhinus mrigala, exotic carps such as silver carp Hypophthalmichthys molitrix, grass carp Ctenopharyngodon idella, common carp Cyprinus carpio and a catfish Sperata seenghala) were examined for the presence of myxozoan parasites infecting gills. Firstly, the gills were examined under a zoom-stereomicroscope for the presence of plasmodia. The number of plasmodia per gill was counted to determine the index for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
(18 reference statements)
3
15
0
Order By: Relevance
“…However, Kaur and Katoch (2016) reported 65.15% (418 out of 1380 fishes) of native carp fish had mixed infection of Myxozoan species at a time and that result was slightly similar to this study. Multiple infections might be occurring due to sharing the same habitat by the host.…”
Section: Resultssupporting
confidence: 89%
“…However, Kaur and Katoch (2016) reported 65.15% (418 out of 1380 fishes) of native carp fish had mixed infection of Myxozoan species at a time and that result was slightly similar to this study. Multiple infections might be occurring due to sharing the same habitat by the host.…”
Section: Resultssupporting
confidence: 89%
“…There are alarming economical losses due to Myxobolus spp. infestation of the major carp in the nursery ponds as reported by Sanaullah and Ahmed (1980), Kaur and Katoch (2016), Kaur and Ahmad (2016) and Ahmad and Kaur (2017). The present study was therefore undertaken to investigate the prevalence rate, site preference and extent of damage caused by myxosporidian parasites in Punjab, India.…”
Section: Introductionmentioning
confidence: 83%
“…Dermal lesion by Myxobolus and Thelohanellus were recorded to be common in the states of Andhra Pradesh and Karnataka (Kalavati and Nandi 2007). The most recent study by Kaur and Katoch (2016) have reported 3 gill infecting Thellohanellus species (T.bifurcata, T.dykovae, T. filli), 1 infecting liver (T. wallagoi) and 2 species infecting fins (T. boggoti, T. kalavatae). The studies conducted by Haldar (1998, 2003) have shown that hybrid carps were more susceptible to myxozoan infestation and in many instances they prove to be more prone to pathogenic effects leading to heavy mortality in culture systems.…”
Section: Prevalencementioning
confidence: 99%
“…Mondal et al (2014) recorded 12.5 % fin infection in L. rohita with T. caudatus (Pagarkar and Das 1993;Kaur et al 2015). Recently, Kaur and Katoch (2016) recorded 3 gill infecting Thelohanellus species in two locations i.e. gill lamellae (LV3 type) and gill filament (FV1 type), causing mild to severe histopathological changes.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation